(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, an effort is made to reduce the size, weight and cost of Electric Vehicles (EVs) with the reconfiguration of propulsion motor topology. The new machine topology has been advantageously used to replace the conventional motors. A Twin Rotor Axial Flux Induction Machine (TRAFIM) having higher power densities, shorter axial lengths than classical Radial Flux Machines have been implemented in this work. This further reduces the other complexities associated with the mechanical differential which is indented to provide different speeds to two wheels in necessary conditions. The performance of EV has been remarkably improved with the proposed reconfiguration. This paper presents a comprehensive analysis of an EV with the adoption of Twin Rotor Axial Flux Induction Machine (TRAFIM).